Analysis of Factors that Influence the Work Accidents on Health Center Staff of Matang Pudeng - Siti Aryanti; Tri Niswati Utami; Nur Aini (Newinera Publisher, 2022)
This study aims at investigating the effect of supervision, OHS training, availability of PPE, work units and standard operating procedures on work accidents of staff at Matang Pudeng Health Center. This research is a descriptive analytical study with a cross sectional approach. The population was all staff of Matang Pudeng Health Center amount 82 people and all was sampled by total sampling. Analysis of the data used univariate, bivariate and multivariate. The results of the chi square test showed that supervision has no effect on work accidents, OHS training has no effect on work accidents, the availability of PPE has no effect on work accidents, work units have no effect on work accidents and SOPs have no effect on work accidents. Logistic regression test showed that the most influential variable on work accidents was SOP. The conclusion of this study is that supervision, OHS training, availability of PPE and SOPs simultaneously affect work accidents. Scheduling its supervision, providing a special budget for the provision of PPE, and giving sanctions to workers who do not work according to procedures. Logistic regression test showed that the most influential variable on work accidents was SOP. The conclusion of this study is that supervision, OHS training, availability of PPE and SOPs simultaneously affect work accidents. It is suggested to the Health Center to do the OHS socialization, scheduling its supervision, providing a special budget for the provision of PPE, and giving sanctions to workers who do not work according to procedures.